Chicken Feather Waste As Adsorbent for Crude Oil Clean Up From Crude Oil Polluted Water - OKOYA, A. A. (International Journal of Psychosocial Rehabilitation, 2020)
This study assessed the adsorption potentials of chicken feather waste (CFW) in Nigeria for the crude oil removal from crude oil polluted water (CPW) in comparison with commercial activated carbon (CAC). This was with a view to providing information on the efficacies of the CFW as an adsorbent. The pulverized chicken feathers were characterized using Rutherford Backscattering Spectrometer (RBS) and Scanning Electron Microscope (SEM) for elemental composition and the determination surface morphology, respectively. Factors such as initial concentration, adsorbent dosage, pH, and contact time were optimized using standard methods. The batch adsorption experiments were carried out for the removal of crude oil from CPW using the CFW and CAC. The data obtained were subjected to one-way analysis of variance. The elemental composition of the CFW showed the presence of Na, Mg, Al, P, K, Ca, Ti, Cr, Mn, Fe, Cu, Zn, Sr, Zr, Cd, Sn, Pb and Si within the range 12.8 - 22566.3 ppm with agglomeration of particle. There was distinctive irregular morphology with large surface area of the CFW. CAC exhibited a high percentage removal efficiency ranging from 88.51 to 96.75%, while CFW ranged from 99.76 to 99.95% for crude oil removal for all initial concentrations (1/3 to 5/3 v/v crude oil/water). Best adsorbent dosage for the crude oil removal for CFW was 25 g, at 50 min contact time, pH 12 and 5/3 (v/v crude oil /water) initial concentration. The order of percentage removal efficiencies of the crude oil by the adsorbents were CFW (98.20 – 99.95) > CAC (82.63 – 95.08). The study concluded that chicken feathers could be an effective adsorbent for the removal of crude oil from crude oil polluted water.